2018
DOI: 10.4274/tjo.56588
|View full text |Cite
|
Sign up to set email alerts
|

Visual Results Following Implantation of a Refractive Multifocal Intraocular Lens in One Eye and a Diffractive in the Contralateral Eye

Abstract: ObjectivesTo assess the visual outcomes in patients who underwent cataract surgery with multifocal intraocular lens (IOL) implantation using a “mix and match” approach.Materials and MethodsTwenty patients (40 eyes) were involved in this prospective, nonrandomized study. Refractive multifocal IOLs (ReZoom NXG1) were implanted in patients’ dominant eyes and diffractive multifocal IOLs (Tecnis ZMA00) were implanted in their non-dominant eyes. Monocular and binocular uncorrected distance, intermediate and near vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Follow-up included visual acuity examination, biomicroscopy, IOP measurement, and fundoscopy. Posterior capsule opacification (PCO) and clinically significant IOL decentration were examined as well [7]. Monocular uncorrected distance visual acuity (UCDVA) and monocular best-corrected distance visual acuity (BCDVA) were evaluated using the Logarithmic Visual Acuity Chart "ETDRS" R n °2110 (Precision Vision, Woodstock, IL, USA) and an illuminator cabinet (Precision Vision, Woodstock, IL, USA) at 4 m distance.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Follow-up included visual acuity examination, biomicroscopy, IOP measurement, and fundoscopy. Posterior capsule opacification (PCO) and clinically significant IOL decentration were examined as well [7]. Monocular uncorrected distance visual acuity (UCDVA) and monocular best-corrected distance visual acuity (BCDVA) were evaluated using the Logarithmic Visual Acuity Chart "ETDRS" R n °2110 (Precision Vision, Woodstock, IL, USA) and an illuminator cabinet (Precision Vision, Woodstock, IL, USA) at 4 m distance.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Furthermore, the multizonal IOL design may lead to a loss of contrast sensitivity associated with the distribution of the total available light between several focal points [ 3 ]. While clinical studies have found better contrast sensitivity after the implantation of diffractive IOLs rather than refractive ones, some authors have disagreed with these findings and reached the opposite conclusions [ 6 , 7 ]. The limitations of concentric-refractive technology may be addressed by the introduction of a multi-segmented approach with alternating focal zones.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that complaints such as photic phenomena are more often reported by patients with MF-IOLs than with MNF-IOLs [ 24 ]. However, no statistically significant differences in halos and glare were found between refractive and diffractive MF-IOLs [ 25 ]. Our previous study [ 9 ] demonstrated that the patients treated with an exchange to another MF-IOL had better satisfaction than an exchange to a MNF-IOL.…”
Section: Discussionmentioning
confidence: 99%